A pharmacokinetic and residual study of sulfadiazine/trimethoprim in mandarin fish (Siniperca chuatsi) with single‐ and multiple‐dose oral administrations. Issue 3 (15th December 2015) - Wang, W.; Luo, L.; Xiao, H.; Zhang, R.; Deng, Y.; Tan, A.; Jiang, L.
Abstract : A pharmacokinetic and tissue residue study of sulfadiazine combined with trimethoprim (SDZ/TMP = 5/1) was conducted in Siniperca chuatsi after single‐ (120 mg/kg) or multiple‐dose (an initial dose of 120 mg/kg followed by a 5‐day consecutive dose of 60 mg/kg) oral administrations at 28 °C. The absorption half‐life ( t 1/2 α ), elimination half‐life ( t 1/2 β ), volume of distribution (Vd /F), and the total body clearance (ClB /F) for SDZ and TMP were 4.3 ± 1.7 to 6.3 ± 1.8 h and 2.4 ± 1.0 to 3.9 ± 0.9 h, 25.9 ± 4.5 to 53.0 ± 5.6 h and 11.8 ± 3.5 to 17.1 ± 3.4 h, 2.34 ± 0.78 to 3.67 ± 0.99 L/kg and 0.39 ± 0.01 to 1.33 ± 0.57 L/kg, and 0.03 ± 0.01 to 0.06 ± 0.01 L/kg·h and 0.02 ± 0.01 to 0.05 ± 0.01 L/kg·h, respectively, after the single dose. The elimination half‐life ( t 1/2 β ) and mean residue time (MRT) for SDZ and TMP were 68.8 ± 7.8 to 139.8 ± 12.3 h and 34.0 ± 5.5 to 56.1 ± 6.8 h, and 99.3 ± 6.1 to 201.7 ± 11.5 h and 49.1 ± 3.5 to 81.0 ± 5.1 h, respectively, after the multiple‐dose administration. The daily oral SDZ/TMP administration might cause a high tissue concentration and long t 1/2 β, thereby affecting antibacterial activity. The withdrawal time for this oral SDZ/TMP formulation (according to the accepted guidelines in Europe for maximum residue limits, <0.1 mg/kg of tissues for sulfonamides, and <0.05 mg/kg for TMP) should not be <36 days for fish.